Something hazy drifting in the air…. Issue 6 (19th December 2019) - McCreary, David; McArdle, Jane; Minks, David; Horridge, Karen
Abstract : : A 7-year-old boy with a background of autism presented to the paediatric emergency department with his left arm 'feeling strange' then became difficult to rouse. On examination, he was found to have left arm weakness and a left-sided facial droop without forehead muscle involvement. Three hours later, his symptoms had completely resolved and he was suspected to have had a first seizure. He was admitted for observation and an electroencephalography which showed slower rhythms in the right posterior quadrant, which was reported as within normal appearances for his age. He was discharged home the following day. Three days later he became lethargic and vomited. His parents reported dysphasia with use of single-word phrases only, he also appeared confused. He re-presented to the paediatric emergency department, where he was found to have increased tone in the left arm, ankle clonus and an upgoing plantar reflex on the left hand side. Questions: What are the differential diagnoses and what investigations should be considered? What type of imaging modality has been used for figures 1 and 2 and what do they show? What type of imaging is used in figures 3 and 4 and what do they show? What is the difference between moyamoya disease and moyamoya syndrome? Histologically in what way does MMD affect the cerebral vasculature? What are the different types of MMD? What are the management strategies used in MMD? Answers can be found on page 2.